درجة تفعيل مديري ومديرات مدارس التعليم الأساسي وما بعد الأساسي للشراكة بين المدرسة والمجتمع المحلي في محافظة الداخلية بسلطنة عمان من وجهة نظر مديري المدارس فيها - المعايطة، عبدالعزيز عطا الله; الهنائية، وسيلة سليمان (جامعة الكويت - مجلس النشر العلمي, 2021)
الأهداف: هدفت هذه الدراسة إلى تعرف درجة تفعيل مديري ومديرات مدارس التعليم الأساسي وما بعد الأساسي للشراكة المجتمعية بين المدرسة والمجتمع المحلي في مدارس محافظة الداخلية بسلطنة عمان من وجهة نظر المديرين، وتعزي إلى متغيرات النوع الاجتماعي، المؤهل العلمي وسنوات الخبرة. المنهج: تكون مجتمع الدراسة من جميع مديري ومديرات مدارس التعليم الأساسي وما بعد الأساسي في محافظة الداخلية للعام الدراسي 2018/ 2019، والبالغ عددهم 210 مديرين ومديرات، وقد تكونت عينة الدراسة من 160 مديرا ومديرة، ولتحقيق أهداف الدراسة، تم تطوير استبانة اشتملت على 30 فقرة موزعة على خمسة مجالات هي: الشراكة في التخطيط المدرسي، الشراكة في تقديم الدعم المالي للمدرسة، الشراكة في الرؤية والأهداف العامة للعملية التعليمية، الشراكة في تقديم الاستشارات للمدرسة، والشراكة في الشؤون الإدارية للمدرسة. النتائج: قد توصلت الدراسة إلى النتائج التالية: أين دور مديري مدارس التعليم الأساسي وما بعد الأساسي في تفعيل الشراكة بين المدرسة والمجتمع المحلي جاء بدرجة متوسطة. جاء ترتيب مجالات الدراسة في دور مديري مدارس التعليم الأساسي وما بعد الأساسي في تفعيل الشراكة بين المدرسة والمجتمع وفق الترتيب الآتي: الشراكة في التخطيط المدرسي، الشراكة في تقديم الدعم المالي للمدرسة، الشراكة في الرؤية والأهداف العامة للعملية التعليمية، الشراكة في تقديم الاستشارات للمدرسة، الشراكة في الشؤون الإدارية للمدرسة. عدم وجود فروق ذات دلالة إحصائية لمتغير النوع الاجتماعي عدا مجال الشراكة في التخطيط المدرسي، وكذلك عدم وجود فروق ذات دلالة إحصائية تعزي لمتغير المؤهل العلمي على المجالات كافة، وكذلك عدم وجود فروق ذات دلالة إحصائية تعزي لمتغير سنوات الخبرة وعلى المجالات كافة. الخاتمة: ختاما نوجه هذه الدراسة إلى المسؤولين في سلطنة عمان لتفعيل تلك الشراكة بين المدرسة والمجتمع المحلي في محافظة الداخلية بسلطنة عمان.
Objectives: This study aimed at identifying the degree of community partnership activation by the headmasters and headmistresses of the basic and post-basic schools between the school and the local community in the schools of Al Dakhiliyah Governorate in the Sultanate of Oman from the point of view of headmasters and headmistresses when attributed to gender variable, academic qualification, and years of experience. Method: The study population consisted of all headmasters and headmistresses of basic and post-basic schools in the Al Dakhiliyah Governorate for the academic year 2018/2019. The sample consisted of 210 school male and female principals and the sample consisted of 160. In order to achieve the objectives of the study, a questionnaire was developed containing 30 paragraphs covering five areas: Partnership in school planning, partnership in providing financial support to the school, partnership in the vision and general objectives of the educational process, partnership in providing consultancy to the school, and partnership in schools' administrative affairs. Results: The study reached that the role of heads of basic and post-basic education schools in activating the partnership between the school and the local community was in a medium degree. The study outcomes also arranged areas of study in the role of heads of basic and post-basic education in activating the partnership between the school and the society according to the following arrangement: partnership in school planning, partnership in providing financial support to the school, partnership in vision and general objectives of the educational process, partnership in providing consultancy to the school, and partnership in school administration. The paper also found no statistical differences for the gender variable except for the area of in the school planning, and no statistical differences attributed to the variable of the scientific qualification in all fields, as well as no statistical differences attributed to the variable of years of experience in all fields. Conclusion: This study is directed to the officials in the Sultanate of Oman to activate this partnership between schools and local community in Al Dakhiliyah Governorate.
Keywords: الإدارة التربوية -- مديرو المدارس -- الشراكة المجتمعية -- التعليم الأساسي -- سلطنة عمان